DEVELOPMENT OF PUBLIC PERCEPTION OF POLICE QUESTIONNAIRE-URDU - Sadiq Hussain* (Pakistan Journal of Psychology, 2023)
The present study was conducted to develop a measure to assess public perception of the police in national context that will be used to understand different dimensions of public perception of the police. To develop the questionnaire, guidelines recommended by DeVellis (2003) were used. The final formatted questionnaire was administered on 750 (378(50.4%) females) community sample representing all districts of Gilgit-Baltistan (GB) except Diamer. Exploratory factor analysis was performed after fulfilling its preconditions. Exploratory factor analysis on 691 (342 (49.5%) females) participants with varimax rotation produced the 13-item Public Perception of the Police Questionnaire-Urdu (PPPQ-U) with three dimensions; public confidence in police, monitoring of police performance, and respect of human rights. Confirmatory factor analysis was applied to establish psychometric properties of two PPPQ-U dimensions and third one was not included because its Cronbach’s alpha was below acceptable level. Results showed acceptable goodness-of-fit and internal reliability. It is recommended to use the PPPQ-U as linguistically accurate and psychometrically sound instrument to assess different dimensions of public perception of the police to select suitable interventions for improvisation of police performance.